U. K. Stukalich – literary critic, historian, local history specialist of the 19th century: linguistic heritage - Gaponenko, Iryna A. (Journal of the Belarusian State University. Philology, 2023)
Biographical information about the literary critic, historian, and local history specialist of the 19th century, U. K. Stukalich, is provided. His views on the formation of Belarusian national and socio-cultural identity are examined. Linguistic heritage of U. K. Stukalich, opinions regarding the past of the Belarusian language and prospects for its development, as well as his remarks and comments on the linguistic research of his linguist contemporaries, are analysed.